Pola Kemitraan Peternak Ayam Broiler (Studi Kasus Di Kecamatan Sukamulya Kabupaten Tangerang) - Sulaeni Sulaeni; Andjar Astuti; Agnes Amelia Siwabesy (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
Broiler Chicken Farm Partnership Patterns (Case Study in Sukamulya District, Tangerang Regency). Broiler chickens are the type of chicken that has the highest meat-producing productivity. Demand for chicken meat requires a production system that involves capital and the community in a partnership for mutual benefits. There are several forms of partnerships with the same goal of making a profit. This study lasted 5 - 6 months with several considerations. research location in Sukamulya District, Tangerang Regency. This research is descriptive quantitative with survey methods and research instruments in the form of interviews and questionnaires as well as analysis tools in the form of calculating income, revenue, and the R / C ratio to see what partnership patterns are used by company A and company B on breeders in Sukamulya District and which partnership patterns the results are more profitable for breeders in Sukamulya District. From this research, it can be ignored that the partnership pattern applied is the plasma core partnership pattern and operational cooperation with the highest income at company B of Rp. 50.544.254,67,- and R/C Ratio 1,808 which uses a partnership pattern of operational cooperation with a 40:60 profit-sharing system, while company A gets the lowest income of Rp. 13.459.820,70 and an R/C Ratio of 1,091 by applying a plasma core partnership pattern.